A UK survey of nutritional care pathways for patients with COVID‐19 prior to and post‐hospital stay. Issue 4 (12th May 2021) - Lawrence, Victoria; Hickson, Mary; Weekes, C. Elizabeth; Julian, Anna; Frost, Gary; Murphy, Jane
Abstract: Background: During the global COVID‐19 pandemic, UK dietitians have delivered the best care to help patients recover from the infection. The present study examined the development and evaluation of care pathways to manage nutritional care of patients following COVID‐19 infection prior to and after discharge. Methods: Registered UK dietitians completed an online questionnaire comprising 26 questions about the development of a pathway, its use, evaluation and training needs. Results: Of 57 responses from organisations, 37 (65%) were involved in the planning/management of nutritional care. Only 19 responses had a new or adapted COVID‐19 pathway. Of these, 74% reported involvement of dietetic services, 47% reported > 1 eligibility criteria for pathway inclusion and 53% accepted all positive or suspected cases. All respondents used nutritional screening, first‐line dietary advice (food first) and referral for further advice and monitoring. Weight and food intake were the most used outcome measure. All pathways addressed symptoms related to nutrition, with the most common being weight loss with poor appetite, not being hungry and skipping meals in 84% of pathways. Over half of respondents (54%) planned to evaluate their pathway and 83% reported that they were 'very or reasonably confident' in their team's nutritional management of COVID‐19. Less than half (42%) reported on training needs. Conclusions: Despite challenges encountered, pathways were developed and implemented. Dietitians had adapted to new ways of working to manage nutritional care in patients prior to and after discharge from hospital following COVID‐19 infection. Further work is needed to develop strategies for evaluation of their impact. Abstract : The present study examined the development of care pathways by UK dietitians to manage the post‐hospital nutritional care of patients following COVID‐19 infection and the evaluation of these pathways. Of the responses, 51% reported developing or adapting a pathway for COVID‐19 infection and 54% planned to undertake evaluation of their pathway. Despite challenges encountered, dietitians have responded rapidly and adapted to new ways of working.